(untitled) (Portuguese Journal of Family Medicine and General Practice, 2022)
In recent decades, there has been a significant change in the age structure of the population consequence of progressive aging, with an increase in the incidence of chronic and degenerative diseases, disabilities, and dependency. Among the health problems affecting elders, dementia syndromes and their complications, such as hypersexuality, have a pronounced impact on family structure and society, with strong implications for the use of health care services. A literature review was carried out on the approach to hypersexuality in dementia, concluding that there is little research on the subject and, consequently, clinical guidelines, which creates difficulties in its identification and approach. The aim of this article is to promote critical reflection on this problem and raise awareness among health professionals for its recognition, adequate approach, and carrying out research for the creation of clinical guidelines.